Detection and Quantification of GABA and Melatonin Contents in Five Hypnotic Medicinal Plants using Chromatography-Based Techniques: Detection of GABA and Melatonin in Hypnotic Plants - Talebi, Marjan; Obeid, Malak; Mojab, Faraz (Iranian Journal of Pharmaceutical Sciences, 2024)
Over the years, medicinal plants have been considered promising treatments for managing various disorders. Numerous natural products contain prospective potential for the treatment of insomnia. This study aimed to determine the quantities of melatonin and GABA present in five plant extracts with hypnotic effects. Five plants were selected for investigation, including Valeriana officinalis, Passiflora incarnata, Aloysia citriodora, Withania somnifera, and Lavandula officinalis. The ethanolic extracts of these plants were prepared using the maceration method. For preliminary phytochemical evaluations, HPTLC fingerprinting was conducted on both the extracts and the standards, including melatonin and GABA. GABA content was determined using HPTLC in three out of the five plants. Furthermore, the HPLC method was used to confirm the presence of melatonin. The results of HPTLC fingerprinting revealed that the ethanolic extracts of Aloysia citriodora, Passiflora incarnata, and Withania somnifera contained GABA, which could be attributed to their reported hypnotic effects. Conversely, none of the five plants contained melatonin, indicating that the hypnotic effect was not related to this compound. In conclusion, this study described the HPTLC method for detecting and quantifying GABA in Withania somnifera and Aloysia citriodora for the first time. Notably, Withania somnifera exhibited the highest amount of GABA.